Pengetahuan tentang penanganan pertama cedera olahraga pada siswa akademi sepak bola - Sri Mulyati Rahayu; Maria Ulfah jamil; Inggrid Dirgahayu; Wempi Budiana; Herlina Husein; Diana Ulfah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2023)
Introduction: Football is a form of physical activity that can be played by both men and women. This sport is inseparable from the use of the feet which involve body structures such as joints and muscles. The problem that often occurs in soccer players is experiencing injuries that can occur to the ankles due to sprains or collisions between players. Serious injury can occur if there is a hard impact on the neck and head area. Sports injuries can cause disturbances in physical activity, psychology, and achievement. The solution to dealing with repetitive sports injuries is by providing education about the first treatment for soccer sports injuries. Purpose: To increase knowledge in the first handling of soccer sports injuries to students at the Ebod Jaya Football Academy and Cimahi FC. Methods: Descriptive with pre-test and post-test design. Population is 60 students, sample is 35 students, with purposive sampling technique. Results: The results obtained were that more than half of the respondents had insufficient knowledge about the first handling of soccer sports injuries before being given education (54%) and more than half of the respondents had sufficient knowledge about the first handling of soccer sports injuries after being given education (69%). Conclusion: Half of the respondents had sufficient knowledge about the first treatment for soccer sports injuries after being given education. Keywords: Knowledge; First Handling; Injury; Football. Pendahuluan: Olahraga sepak bola merupakan bentuk aktivitas fisik yang bisa dimainkan oleh laki-laki maupun perempuan. Olahraga ini tidak terlepas dari penggunaan kaki yang melibatkan struktur tubuh seperti sendi dan otot. Permasalahan yang sering terjadi pada pemain sepak bola adalah mengalami cedera yang dapat terjadi pada pergelangan kaki akibat terkilir atau benturan antar pemain. Cedera berat dapat terjadi jika ada benturan keras pada daerah leher dan kepala. Cedera olahraga dapat menimbulkan gangguan aktivitas fisik, psikis, dan prestasi. Solusi untuk mengatasi cedera olahraga berulang dengan diberikan edukasi tentang penanganan pertama cedera olahraga sepak bola. Tujuan: Untuk meningkatkan pengetahuan dalam penanganan pertama cedera olahraga sepak bola pada siswa Akademi sepak bola Ebod Jaya dan Cimahi FC. Metode: Deskriptif dengan pre-test dan post-test design. Populasi 60 siswa, sampel 35 siswa, dengan teknik purposive sampling. Hasil: Hasil yang didapatkan lebih dari setengah responden memiliki pengetahuan kurang tentang penanganan pertama cedera olahraga sepak bola sebelum diberikan edukasi (54%) dan lebih dari setengah responden memiliki pengetahuan cukup tentang penanganan pertama cedera olahraga sepak bola setelah diberikan edukasi (69%). Simpulan: Setengah responden memiliki pengetahuan cukup tentang penanganan pertama cedera olahraga sepak bola setelah diberikan edukasi.